Petit Face Mask. A clinical alternative for the treatment of class III (Research, Society and Development, 2023)
Class III malocclusion is characterized by an abnormal anteroposterior relationship between the maxilla and mandible, where, in many cases, an anterior crossbite relationship occurs. It can be intercepted during the craniofacial growth and development phase through the use of orthopedic devices. Thus, early treatment allows to redirect growth in a more favorable way. This work aimed to describe the treatment and show the results of the therapy in a patient in the mixed dentition phase with Angle Class III malocclusion. Female patient, 9 years old, Leocoderma, sought orthodontic treatment at the Specialization Course in Orthodontics at the Advanced Postgraduate Unit FACOP – Manaus/AM, promoted by the Instituto Brasileiro de Ensino do Norte – IBEN, with the main complaint "wrong bite". With Angle Class III malocclusion and anterior crossbite, the proposed plan was orthopedic treatment of reverse traction of the maxilla with a Mcnamara breaker and a Petit face mask. After the correct and disciplined use of these appliances by the patient, the correction of the Class III malocclusion was achieved, the uncrossing of the anterior bite bite, improvement in the maxillomandibular relationship and a more harmonious smile. Subsequently, the use of fixed appliances was introduced for the proper alignment/leveling of the dental elements.